Evaluating Expression and Potential Diagnostic and Prognostic Values of Survivin in Bladder Tumors: A Preliminary Report - Mowla, Seyyed Djavad; Emadi Baygi, Mojtaba; Ziaee, Seyyed Amirmohsen; Nikpoor, Parvaneh (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Lotus; mso-font-alt:"Courier New"; mso-font-charset:178; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:8193 0 0 0 64 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Survivin, an inhibitor of apoptosis (IAP), has been reported to be capable of regulating both cellular proliferation and apoptotic cell death. Survivin expression has been described during embryonic development and in adult cancerous tissues, with greatly reduced expression in adult normal differentiated tissues, particularly if their proliferation index is low. In the present study,the expression and potential diagnostic and prognostic value of survivin in bladder tumors was evaluated. Materials and Methods: Primary and recurrent bladder tumor specimens were obtained from patients referred to the Shaheed LabbafinejadMedical Center in Tehran, Iran.Total RNA was isolated from frozen tissues, reverse transcribed and amplified by means of a nested polymerase chain reaction technique. Results: Survivin was detected in 3 cases of primary tumors (42.8%) and 6 cases of recurrent tumors of bladder (60%). Survivin-?Ex3 expression was seen in 41.2% of the 17 cases with bladder cancer. Conclusion: Our findings suggest that the expression of survivin and survivin-?Ex3 is well associated with invasive and more-aggressive forms of bladder cancer. Our data also indicate that the presence of survivin-?Ex3 is better correlated with tumorigenesis of bladder cancer compared with survivin expression.